1985
DOI: 10.2190/avmm-36f4-d3v8-t5d0
|View full text |Cite
|
Sign up to set email alerts
|

Subconscious Percepts as “Unmonitored” Percepts: An Empirical Study

Abstract: In exp1ainingunattended or "subconscious" perception, Dixonian theory supposes that unattended percepts are unconscious. Alternatively, the theory of cognitivestate monitoring supposes that one's unattended percepts are conscious sensations, which are accompanied by no selfconsciousness that one is perceiving, rather than imaging, them. Consistent with the latter theoretical supposition, the results of the current experiment show that previously unattended stimuli are memorially indistinguishable both from pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1987
1987
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Kunzendorf (1984) and Kunzendorf and Butler (1992) conducted comparative tests of Dixon's latter argument for sensationless preconscious perception and Fechner's historic argument for conscious sensation without self-conscious apperception. Kunzendorf (1984) found that subjects were memorially unable to distinguish between visual sensations previously imagined and visual sensations previously perceived in the periphery of the visual field, and concluded that the unattended sensations in the periphery were subconsciously perceived sensations-conscious sensations unaccompanied by any self-conscious apperception or any self-conscious monitoring of their perceptual (vs. imaginal) source. Kunzendorf and Butler (1992) experimentally tested Julesz's (1971) assertion that, during the "cyclopean perception" of random-dot stereograms, monocular input to the stereogram is processed nonconsciously.…”
Section: Research On Self-conscious Source Monitoring and Subconsciou...mentioning
confidence: 99%
“…Kunzendorf (1984) and Kunzendorf and Butler (1992) conducted comparative tests of Dixon's latter argument for sensationless preconscious perception and Fechner's historic argument for conscious sensation without self-conscious apperception. Kunzendorf (1984) found that subjects were memorially unable to distinguish between visual sensations previously imagined and visual sensations previously perceived in the periphery of the visual field, and concluded that the unattended sensations in the periphery were subconsciously perceived sensations-conscious sensations unaccompanied by any self-conscious apperception or any self-conscious monitoring of their perceptual (vs. imaginal) source. Kunzendorf and Butler (1992) experimentally tested Julesz's (1971) assertion that, during the "cyclopean perception" of random-dot stereograms, monocular input to the stereogram is processed nonconsciously.…”
Section: Research On Self-conscious Source Monitoring and Subconsciou...mentioning
confidence: 99%